1994
DOI: 10.1099/00221287-140-4-779
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a ferulic acid esterase (FAE-III) from Aspergillus niger: specificity for the phenolic moiety and binding to microcrystalline cellulose

Abstract: An inducible ferulic acid esterase (FAE-Ill) has been isolated, purified and partially characterized from Aspergillus niger after growth on oat spelt xylan. The purification procedure utilized ammonium sulphate precipitation, hydrophobic interaction and anion-exchange chromatography. The purified enzyme appeared almost pure by SDS-PAGE, with an apparent M, of 36000. A single band, corresponding to a pl of 3.3 was observed on isoelectric focusing. With methyl ferulate as substrate, the enzyme had a specific act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
108
9
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(130 citation statements)
references
References 29 publications
(26 reference statements)
11
108
9
2
Order By: Relevance
“…Type A enzymes such as A. niger FAE II 37) and FAE III 38) are inactive towards MCA. Type B enzymes such as A. niger FAE I 37) and CinnAE 39) are not able to hydrolyze MSA.…”
Section: Discussionmentioning
confidence: 99%
“…Type A enzymes such as A. niger FAE II 37) and FAE III 38) are inactive towards MCA. Type B enzymes such as A. niger FAE I 37) and CinnAE 39) are not able to hydrolyze MSA.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial feruloyl esterases that have been purified varied in molecular weight from 24kDa (FAE-II from Neocallimastix strain MC-2 7 ) to132kDa (FAE-I from Aspergillus niger 10 ). In the case of Aspergillus niger three feruloyl esterases have been characterised and their estimated molecular weights are 132kDa (FAE-I), 29kDa (FAE-II) and 36kDa (FAE-III) 10,11 . This suggests that such a variation in molecular weights is not unusual.…”
Section: (-7'977-32mentioning
confidence: 99%
“…It is likely therefore that the removal of the aryl substituents is necessary for the breakdown of the cell wall pentosans. The cell walls of the aleurone layer, the crushed cell layer, the sheaf cells and some parts of the embryo fluoresce strongly in ultraviolet light, while the cell walls of the starchy endosperm fluoresce less strongly [2][3][4]8,11 . The fluorescence is due to the ferulic acid (4-hydroxy-3-methoxy cinnamic acid), which is attached to the C-5 position of some arabinose residues 1,25 .…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…Faulds and Williamson (1994) found that ferulic acid esterase from Aspergillus niger could release ferulic and sinapic acids (3,5-dimethoxy-4-hydroxycinnamic acid), but not p-coumaric or caffeic acids (3, 4-dihydroxycinnamic acid). This indicates that this ferulic acid esterase is active only on methyl esters of certain hydroxycinnamic acids, including ferulic and sinapic esters, but not p-coumaric or caffeic esters.…”
mentioning
confidence: 99%
“…In contrast, ferulic acid esterase from Pseudomonas fluorescens subsp. Cellulosa is effective on all these methyl hydroxycinnamic esters (Faulds and Williamson 1994), including ferulic acid and p-coumaric acid.…”
mentioning
confidence: 99%